The Influence Of Price, Service Quality And Product Quality On Purchasing Decisions At Syakila Bakery Shop Bengkulu City - Susan Susanti; Yun Fitriano; Tri Febrina Melinda (Journal of Indonesian Management, 2023)
The development of the world of business has made business entrepreneur competitive. Various approaches have been taken to gain consumer sympathy, both through improving advice and infrastructure with high-tech facilities and by developing human resources. There is so much competition and the desire to provide the best to consumers has given consumers the position of decision makers. The increasing number of products types and businesses that are the same or similar to the various services or products offered, makes people make choices according to their needs. The purpose of this research is to determine the extent of the influence of price, service quality and product quality on purchasing decisions at Syakila Bakery shop Bengkulu City. This type of research is quantitative. The method used is a questionnaire. The sample of this research was 150 respondents. The results of the research show that the multiple linear regression obtained Y = 36,781 + -0,293 X1 + 0,237X2 + 0,381 + 4,527. The results of the price test (X1) show t count 4.011 > 1.655 and significance 0.00 < 0.05, so the results of hypothesis Ha is accepted and Ho is rejected, meaning that price has a positive and significant effect on purchasing decisions at Syakila Bakery shop, Bengkulu City. the results of the service quality test (X2) show t count 3,116 > 1,655 and a significant value of 0.000 < 0.05 means Ha is accepted and Ho is rejected. The product quality test results (X3) show t count 5,231 > 1,655 and a significant value of 0.000 < 0.05 meaning Ha is accepted and Ho is rejected. Keywords: Price, Service Quality, Product Quality, Purchasing Decisions. Student (Management) Supervisors